Utilization of Universities’ Massive Online Open Courses in Learning Management System: Research Trends and Bibliometric Analysis - Dwikoranto Dwikoranto; Wuwuh Asrining Surasmi; Benny Kurniawan; Irgy Redityo Dawana; Lindsay N. Bergsma (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: This study aims to explore research trends related to the use of Massive Open Online Courses in Learning Management Systems (MOOCs in LMS) in university environments and to conduct bibliometric analysis to understand research developments related to this topic. Online learning is increasingly popular with the MOOCs in LMS, which allows students to learn flexibly and independently through digital platforms. Method: The data is retrieved from the Google Scholar database, using keywords related to MOOCs in LMS and universities. This study uses a bibliometric analysis method using the Google Scholar and VOSviewer databases, which obtained 1,710 articles. Results: The results show that the use of MOOCs in LMS in the context of university learning has become an increasingly popular research topic in recent years, where the publication rate has increased significantly. This has the potential to be further investigated in the future. Further research related to MOOCs in LMS can be integrated with blended learning models. This is because the Blended learning model using MOOCs can improve critical thinking skills and problem-solving. This research has limitations, namely using only one database, Google Scholar, to obtain research data. Novelty: Therefore, it is recommended that MOOCs in LMS research at universities be carried out using other databases besides Google Scholar to obtain broader data.